2016
DOI: 10.1186/s12985-016-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of coevolution in nonstructural proteins of chikungunya virus

Abstract: BackgroundRNA viruses are characterized by high rate of mutations mainly due to the lack of proofreading repair activities associated with its RNA-dependent RNA-polymerase (RdRp). In case of arboviruses, this phenomenon has lead to the existence of mixed population of genomic variants within the host called quasi-species. The stability of strains within the quasi-species lies on mutations that are positively selected which in turn depend on whether these mutations are beneficial in either or both hosts. Coevol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…To determine the cross‐reactivity profile of the antibodies, each commercially available ZIKV antibody was tested against dengue virus (serogroups 1–4), West Nile virus, Japanese encephalitis virus, yellow fever virus, and chikungunya virus using the established optimal conditions (Table ). Chikungunya virus belongs to the family Togaviridae but shares a similar geographic distribution and clinical presentation to dengue and ZIKV , and therefore was included in the cross‐reactivity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the cross‐reactivity profile of the antibodies, each commercially available ZIKV antibody was tested against dengue virus (serogroups 1–4), West Nile virus, Japanese encephalitis virus, yellow fever virus, and chikungunya virus using the established optimal conditions (Table ). Chikungunya virus belongs to the family Togaviridae but shares a similar geographic distribution and clinical presentation to dengue and ZIKV , and therefore was included in the cross‐reactivity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The deletions arose as the result of CHIKV (Asian) evolutionary adaptation to the specific local setting; for example, the CHIKV (Asian) MY/06/37348 and MY/06/37350 were isolated during a local CHIKV outbreak in Bagan Panchor Perak, Malaysia, in 2006 [225,237,250]. In addition, based on the human eukaryotic linear motif (ELM) predictions, it has been suggested that the deletion motifs might play a role in phosphorylation and virus stability [242]. However, the biological consequence(s) of the nsP3 HVD deletion event still need to be identified [237], and wet lab experiments are needed to deepen our understanding of the role of these deletion motifs in both alphaviruses and their hosts [242].…”
Section: Indel Repetition and Duplication Events In Chikv Nsp3mentioning
confidence: 99%
“…In addition, based on the human eukaryotic linear motif (ELM) predictions, it has been suggested that the deletion motifs might play a role in phosphorylation and virus stability [242]. However, the biological consequence(s) of the nsP3 HVD deletion event still need to be identified [237], and wet lab experiments are needed to deepen our understanding of the role of these deletion motifs in both alphaviruses and their hosts [242].…”
Section: Indel Repetition and Duplication Events In Chikv Nsp3mentioning
confidence: 99%
“…11,[32][33][34] Basically, CHIKV illness severe joint pain in the ankles, fingers, toes, elbow, knees, and wrists. 38,39 In general, CHIKV attacks fibroblasts, suggesting its involvement with muscles, joints, and skin connective tissues. [35][36][37] In 40% of patients were found to still have anti-CHIKV immunoglobulin M (IgM), eighteen months after disease onset.…”
Section: Clinical Aspects Of Chikungunya Infectionmentioning
confidence: 99%